2018
DOI: 10.1007/s10567-018-0269-2
|View full text |Cite
|
Sign up to set email alerts
|

Functioning Among Typically Developing Siblings of Individuals with Autism Spectrum Disorder: A Meta-Analysis

Abstract: The literature on typically developing siblings of individuals with autism spectrum disorder (ASD-Sibs) provides inconsistent results, with some studies reporting ASD-Sibs are more likely to have negative outcomes than comparison groups, and others reporting no significant differences. Therefore, the purpose of this study was to meta-analytically aggregate study effect sizes to more accurately calculate the degree to which ASD-Sibs function similarly or differently compared to siblings of people who do not hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 91 publications
2
55
1
1
Order By: Relevance
“…Moreover, the impact on non-disabled siblings is worthy of attention given the increasing evidence that they fared worse in terms of psychological functioning, internalized behaviour problems, social functioning, and sibling relationships while also showing increased anxiety and depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the impact on non-disabled siblings is worthy of attention given the increasing evidence that they fared worse in terms of psychological functioning, internalized behaviour problems, social functioning, and sibling relationships while also showing increased anxiety and depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, meta-analytic data from 69 independent studies suggest that relative to non-autistic siblings, siblings of autistic children are more likely to have internalising difficulties, poorer psychological and social functioning, and more maladaptive sibling relationships. Conversely, there were no sibling group differences for general psychological adjustment, externalising behaviours, coping skills, or family functioning (Shivers, Jackson & McGregor, 2018).…”
Section: Introductionmentioning
confidence: 66%
“…The results also show that children speak little of their siblings with autism and participate in the sessions spontaneously with all kinds of interventions (liking, disliking, laughter, play, etc.). The communicative richness evident in their behavior patterns reinforces the importance of offering this type of intervention for children with ASD-Sibs (Shivers et al, 2018). The support group helps them think about and of themselves and facilitates their development of a differentiated identity (Fieschi et al, 2011; Centre Educatiu i Terapèutic Carrilet, Alcácer et al, 2013; Venturella et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…In recent years, interest has grown in whether ASD-Sibs have a greater risk of developing emotional and behavioral problems than the general population, with empirical results pointing to enormous variability (Griffith et al, 2014; McHale et al, 2016): some studies affirm an increased risk (Meyer et al, 2011; Shivers et al, 2013; Hastings and Petalas, 2014), others suggest a similar risk (Macks and Reeve, 2007; Ferraioli and Harris, 2009; Walton and Ingersoll, 2015), and yet others argue that ASD-Sibs demonstrate better social adaptation and more positive sibling relationships (Hastings, 2003; Petalas et al, 2012). A recent meta-analysis (Shivers et al, 2018) of 69 studies that compared siblings with ASD-Sibs with siblings without ASD-Sibs found that, for some 800 individual comparisons, children with ASD-Sibs had significantly poorer – albeit small in magnitude – outcomes, specifically in their internalization of behavioral problems, psychological functioning, beliefs, social functioning, and relationships between siblings. No significant results were obtained for adaptation, externalization of behavioral problems, attention-deficit/hyperactivity disorder, coping or family functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation